Relationship between BMI and chemotherapy-induced peripheral neuropathy in cancer patients: a dose-response meta-analysis - Yanbing, Li; Zijun, Li; Hongbo, Zuo; Zhi, Wang (World journal of surgical oncology, 2025)
This meta-analysis aimed to evaluate the dose-response relationship between body mass index (BMI) and the risk of chemotherapy-induced peripheral neuropathy (CIPN) in cancer patients. We conducted a dose-response meta-analysis of 10 studies involving 6,841 cancer patients. Studies reporting BMI and CIPN outcomes were selected. The relationship between BMI and CIPN was assessed using random-effects models and restricted cubic splines to model the dose-response association. Pooled analysis revealed a significant association between higher BMI and increased risk of CIPN, with an odds ratio (OR) of 1.55 (95% CI, 1.20-1.99). A dose-response analysis demonstrated a clear linear relationship between BMI and the risk of CIPN. For every 5 kg/m increase in BMI, the relative risk of CIPN increased by approximately 15%. Subgroup analyses showed stronger associations in breast cancer patients and those treated with taxane or platinum-based regimens. Sensitivity analyses confirmed the robustness of the results, and mild publication bias was observed. Higher BMI is significantly associated with an increased risk of CIPN, with a dose-dependent effect. Weight management interventions, such as dietary modifications and physical activity, may reduce CIPN risk, particularly in patients with elevated BMI undergoing chemotherapy with neurotoxic regimens.